Using “ISAREG” on irrigation management in watermelon cultivation in the Baixo Acaraú, Ceará - Saraiva, Kleiton (2012)
The objective of this study was to apply the ISAREG software model to the irrigation management of watermelon in the Lower Acaraú Irrigated Perimeter (LAIP). To this end, the soil water-balance was analysed, developing an irrigation schedule which aimed for maximum crop yield for the soil and climatic conditions of the LAIP for a specific planting date and comparing it to the irrigation scheme currently adopted by irrigators. With an aim to the practical application of ISAREG, the model was supplied monthly with climatic variables, precipitation and soil data, and information on the crop. Finally, an irrigation option available in ISAREG was selected, and a simulation of the soil water-balance was carried out. Questionnaires were used in order to get information about the irrigation scheme employed at the LAIP. The research showed that the producers of watermelon at the LAIP are not properly managing water resources. During the crop cycle, irrigators are applying an excess of about 215.2 mm of water at some periods, and a deficit of 24.2 mm to the crops in others.